2021
DOI: 10.3390/molecules26061646
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Synthesis of Solution Processable Carbon Nitride Polymers

Abstract: Carbon nitride materials require high temperatures (>500 °C) for their preparation, which entails substantial energy consumption. Furthermore, the high reaction temperature limits the materials’ processability and the control over their elemental composition. Therefore, alternative synthetic pathways that operate under milder conditions are still very much sought after. In this work, we prepared semiconductive carbon nitride (CN) polymers at low temperatures (300 °C) by carrying out the thermal condensation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…In order to study this synthetic approach with a wider variety of precursors, thereby showing its applicability to the synthesis of different materials, we replaced melamine with other precursors commonly employed in the preparation of photoactive polymers, namely urea, [48] dicyandiamide (DCD), [49] acetoguanamine (AGA), [50,51] and 2,4,6‐triaminopyrimidine (TAP), [52,53] and we studied the supramolecular self‐assembly behaviour of the resulting mixture. Amongst those monomers, we observed that only TAP was able to form a bulk hydrogel with cyanobenzoic acid, probably owing to the very similar structure and hydrogen‐bonding ability of TAP and MA [46,54] .…”
Section: Resultsmentioning
confidence: 99%
“…In order to study this synthetic approach with a wider variety of precursors, thereby showing its applicability to the synthesis of different materials, we replaced melamine with other precursors commonly employed in the preparation of photoactive polymers, namely urea, [48] dicyandiamide (DCD), [49] acetoguanamine (AGA), [50,51] and 2,4,6‐triaminopyrimidine (TAP), [52,53] and we studied the supramolecular self‐assembly behaviour of the resulting mixture. Amongst those monomers, we observed that only TAP was able to form a bulk hydrogel with cyanobenzoic acid, probably owing to the very similar structure and hydrogen‐bonding ability of TAP and MA [46,54] .…”
Section: Resultsmentioning
confidence: 99%
“…The C 1s narrow spectrum in Figure 6(a) was deconvoluted into three components: the typical peak at 284.5 eV is assigned to C−C bonded atoms present in adventitious carbon, whereas the peaks 285.8 and 287.5 eV are attributed to C−N=C and C−(N) 3 groups of g‐C 3 N 4 support [36] . The N 1s photoelectron spectrum can be deconvoluted into two peaks centered at approximately 398.5 and 400.2 eV, which related to C−N=C and N−(C) 3 species, indicating the characteristics of graphitic structure of g‐C 3 N 4 [37,38] . Figure 6(c) illustrates the Ni 2p photoelectron spectrum which describes the chemical states of nickel present on the outermost surface of the sample.…”
Section: Resultsmentioning
confidence: 99%
“…[36] The N 1s photoelectron spectrum can be deconvoluted into two peaks centered at approximately 398.5 and 400.2 eV, which related to CÀ N=C and NÀ (C) 3 species, indicating the characteristics of graphitic structure of g-C 3 N 4 . [37,38]…”
Section: Xps Surface Analysismentioning
confidence: 99%
“…This difference indicates a modification of the melaminium chloride hemihydrate structure caused by the additional AGA, whose methyl groups disrupt the crystal growth in a three dimensional fashion (Scheme S1, Figure S2, Supporting Infor mation). [25,26] Unfortunately, we could not grow single crystals of melamine:AGA suitable for SCXRD analysis.…”
Section: Resultsmentioning
confidence: 99%